The Impact of Artificial Intelligence on English Language Teaching: Opportunities and Challenges in Technology Era - Hilmy Ahimsa, Ahmad Fahim; Khawa, Dewi (Institut Agama Islam Negeri Palopo, 2025)
The purpose of this study is to analyze the impact of artificial intelligence (AI) on English language teaching, especially in the context of the English Language Study Program at KH. Mukhtar Syafa'at University Banyuwangi. Along with the development of technology, AI has presented various opportunities and challenges in education. One of the main opportunities is AI's ability to provide personalized learning, where technologies such as chatbots, virtual assistants, and AI-based applications can help students improve language skills independently. This qualitative case study analyzes AI's impact on English teaching at KH. Mukhtar Syafa'at University, Banyuwangi. Data is collected through semi-structured interviews with lecturers and students, participant observation, and document analysis. Thematic analysis identifies key patterns, with source triangulation ensuring validity. Findings explore AI’s benefits, challenges, and its role in enhancing learning. This study aims to provide insights into optimizing AI integration while maintaining effective pedagogy in academic environments. The results of this study show that Artificial intelligence (AI) significantly impacts English learning by enhancing students' self-directed learning with instant feedback. However, excessive reliance on AI may hinder critical thinking and social interaction. Lecturers also face challenges in AI adaptation due to limited training and infrastructure, fearing it may reduce their role. A balanced approach is essential—students should use AI as a learning tool, not a substitute for thinking and communication. Universities must provide training and support to help lecturers integrate AI effectively while maintaining human interaction in education. With proper strategies, AI can enhance learning quality without diminishing educators' roles.